Figs (Ficus Carica L.): cultivation method and production based in Malaysia - Kamaruddin, Shamin Shazwan; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Tajudin, Nur Shuhada (Zibeline International Publishing, 2019)
Ficus (Moraceae) is a tree or shrub natively originated from East Asia countries such as Middle East and Turkey. However, determination of the most suitable cultivation method in Malaysia has becoming one of the major concerns in figs industry. This is because figs can be easily found in cold and temperate regions compared to the equator regions. Therefore, this paper will discuss on the method of figs cultivation and its production based on the market demands in Malaysia. Simple propagation methods such as cutting, and layering are the most recommended method used for cultivating the fig trees. As for the production, figs are mainly processed as food such as jam, tea, dipping sauce, spaghetti sauce and dried processed food or available fresh. It is also used in traditional medicine as it is claimed to be good remedies in treating severe health problem such reducing blood sugar level and gastrointestinal problem.